A rare case of adult-onset Still’s disease with peripheral neuropathy - Buch, Kathan Pankaj; Solanki, Anshu Kishor; Gondaliya, Shrey Rajesh (International Journal of Advances in Medicine, 2025)
Adult onset stills disease is a rare multisystem inflammatory autoimmune disorder which is characterized by a triad of fever, joint pain, and a transient salmon-pink maculopapular rash. Here we present a rare case of 27-year-old female who presented with symptoms of fever, polyarthritis for 2 months, and ulceration of right foot and numbness of left hand for 20 days. The diagnosis of adult-onset Still’s disease (AOSD) was confirmed as patient fulfilled the Yamaguchi criteria. The presentation, diagnostic work up and management is discussed and the current literature pertaining to this interesting case is reviewed.